Primary ciliogenesis requires the distal appendage component Cep123 - James Sillibourne; Ilse Hurbain; Thierry Grand‐Perret; Bruno Goud; Phong T. Tran; Michel Bornens (2013)
Summary Primary cilium formation is initiated at the distal end of the mother centriole in a highly co-ordinated manner. This requires the capping of the distal end of the mother centriole with a ciliary vesicle and the anchoring of the basal body (mother centriole) to the cell cortex, both of which are mediated by the distal appendages. Here, we show that the distal appendage protein Cep123 (Cep89/CCDC123) is required for the assembly, but not the maintenance, of a primary cilium. In the absence of Cep123 ciliary vesicle formation fails, suggesting that it functions in the early stages of primary ciliogenesis. Consistent with such a role, Cep123 interacts with the centriolar satellite proteins PCM-1, Cep290 and OFD1, all of which play a role in primary ciliogenesis. These interactions are mediated by a domain in the C-terminus of Cep123 (400–783) that overlaps the distal appendage-targeting domain (500–600). Together, the data implicate Cep123 as a new player in the primary ciliogenesis pathway and expand upon the role of the distal appendages in this process.